Coordinated Regulation of Iron-Acquisition Genes and Citrate Biosynthesis Drives Seasonal Iron Deficiency Adaptation in ‘Yali’ Pears (Pyrus bretschneideri Rehd.) - Shuilin Liu; Ming Zhang; Huiying Wang; Yue Xu; Chaodie Wen; Jianguang Zhang; Yuxing Zhang; Haiyan Shi (Horticulturae)
Iron deficiency chlorosis severely limits the productivity of ‘Yali’ pears in alkaline soils. This study systematically investigated the physiological and molecular responses of ‘Yali’ pears to varying degrees of iron deficiency, focusing on the roles of PbFRO2 (Pyrus bretschneideri Ferric Reductase Oxidase 2), PbIRT1 (Pyrus bretschneideri Iron-Regulated Transporter 1), and PbCS2 (Pyrus bretschneideri Citrate Synthase 2) in iron uptake and homeostasis. Based on field observations, pear trees were categorized into normal, moderately chlorotic, and severely chlorotic groups. Results demonstrated that moderate iron deficiency upregulated PbFRO2 (2.86–7.09-fold), enhanced root ferric reductase (FCR) activity, and promoted Fe3+ reduction and Fe2+ transport. In contrast, severe deficiency suppressed the expression of these genes and reduced photosynthetic efficiency. Leaf citrate content significantly increased with chlorosis severity, while root citrate content exhibited seasonal fluctuations, peaking in July. Multivariate analyses (PCA and PLS-DA) revealed distinct physiological clustering: normal and moderately chlorotic groups overlapped, whereas the severely chlorotic group formed a separate cluster, reflecting a transition from compensatory activation to metabolic collapse. PbFRO2 emerged as a central regulator, driving root iron storage in spring and redistribution in summer. These findings elucidate a biphasic adaptation strategy, where moderate deficiency triggers gene-mediated iron mobilization, whereas severe stress disrupts homeostasis. This study provides critical insights into iron metabolism dynamics and proposes PbFRO2 as a molecular target for breeding iron-efficient pear cultivars.